Persentase Biaya Bahan Baku, BTK, BOP, Persediaan Dalam Proses dan Barang Jadi Terhadap HPP (Studi Kasus: PT Servo Fire Indonesia) - Aldi Febriansyah; Ratiyah Ratiyah (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2023)
Cost of Goods Sold represents all expenses incurred in the process of producing a product until it is ready for sale. The Cost of Goods Sold structure consists of inventory, labor, and overhead costs. Inventory includes raw material costs, work in progress inventory, and finished goods inventory. Labor refers to the workforce directly involved in the production of traded goods, while overhead costs are expenses related to the manufacturing process. The objective of this research is to determine how to calculate the percentage of Raw Material Costs, Labor Costs, Factory Overhead Costs, Work in Progress Inventory, and Finished Goods Inventory, as well as to understand the influence of these costs and inventories on the Cost of Goods Sold. This research employs a quantitative method with a case study approach, conducting research on a specific object with a limited population, resulting in conclusions applicable only to the studied object and during a specific time frame. In this study, it was found that both costs and inventories significantly affect the Cost of Goods Sold.